Teachers’ Perceptions of Culturally Responsive Teaching in International Programs in Vietnamese Higher Education - Luong, Phuong Minh; Tran, Ly Thi; Dang, Giang Hoang; Vu, Toan Van (Vietnam Journal of Education, 2025)
This article explores teachers’ perceptions of culturally responsive teaching (CRT) within international programs in Vietnam’s universities. In-depth interviews were conducted with 26 teachers from 13 international programs across 8 universities. The thematic analysis of the qualitative data revealed three key themes: promoting cultural diversity and ecosystem-based teaching approaches; contextualising curricula, teaching approaches, assessments and learning environments to ensure the relevance of international programs for students; and fostering equal positions between Vietnamese and foreign teachers, as well as between students in international and mainstream programs. These findings offer valuable insights for stakeholders in Vietnam’s higher education system, highlighting the need to support educators’ professional development in applying CRT effectively within a highly internationalised education.